ANALYSIS OF THE PROBLEM OF THE CERTIFICATION IN THE AUDIT PROFESSION IN THE PUBLIC SECTOR IN THE REPUBLIC OF SERBIA - Jakovljevic, Nemanja (Economic Outlook, 2022)
In the context of the public sector, the key stakeholder is the state, i.e. all citizens of the Republic of Serbia as taxpayers. Therefore, it is important that auditors in the public sector act as citizens of the Republic of Serbia, performing control activities and independent assurance services, and in order to be possible, it is necessary to ensure the existence of relevant and appropriate criteria for their selection. The subject of this paper is the analysis of the issue of certification of persons engaged in auditing in the public sector in the Republic of Serbia by performing a comparative analysis of conditions and programs for acquiring professional titles in the field of internal audit most often represented in the Republic of Serbia. The main conclusion is that there are differences in the conditions and programs, which are most pronounced in the domain of the number of exams taken, as well as the average time required to acquire a professional title.
Keywords: Keywords: audit, public sector, certification.